KELEMBAGAAN DALAM PENGELOLAAN SAMPAH UNTUK PENINGKATAN KEBERSIHAN DI KOTA BANDUNG - Raden Mohamad Mulyadin; Kuncoro Ariawan; Indah Bangsawan; Subarudi Subarudi; Mohammad Iqbal (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2023)
One of the social problems facing in Bandung City (BC) is waste problem because waste production and pollution affect not only the aesthetics, cleanness, and convenience of the city, but also people’s health and the city environment. This problem rises as the population grows that produce more household waste, meanwhile, the institution of waste management is weak. An institution is an organization with its supporting infrastructure such as regulation, authority, work mechanism, human resources, and financial system. This research aims to analyze waste management in BC from its institutional aspect. The data from selected respondents are collected through questionnaire and depth interviews. The data were analyzed by using a qualitative descriptive method. The research revealed that the BC Government has to obligate UU No. 18/2008 by issuing local regulations and Mayor regulations related to waste management. PD Kebersihan established since 1985 has not optimally conducted and finally it is liquidated. The new cleanliness institution replacing PD Kebersihan should continue the previous good program and improve the less optimal program of waste management. It is hoped that Bandung Major has to set up a priority-scale of waste management program that is synergized with the medium term planning of Bandung City.